(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this article we claim that only applying a thorough method of morphological segmentation on substrata research we may draw a validated set of units, akin to be used in comparison or reconstruction of substrata languages. Furthermore, we contend the view that our reconstruction of Palaeosardinian has benefited from the application of a rigourous morphological segmentation, and hence the deduced results exhibit the same degree of validity we attach to reconstructed items of Iberian or Protovasconian. Our contention challenges the traditional view that cognates between substrata reconstructed systems are exclusively to be put down to chance. Lastly, we put forward the hypothesis that the reconstructed Palaosardinian displays an unquestionable linking with Palaeovasconian, so that its insertion within a new Stammbaum of this Palaeohispanic languages cannot be dismissed out of hand.